IMPLEMENTASI ACTIVITY BASED MANAGEMENT (ABM) UNTUK MENINGKATKAN EFISIENSI BIAYA PRODUKSI PADA BENGKEL LAS KARYA INDAH 2 DI KABUPATEN MALANG - Novitasari, Yuliani; Djajanto, Ludfi; Berlianingtyas, Putri Ayu (Unit Penelitian dan Pengabdian kepada Masyarakat Politeknik TEDC Bandung Jl. Pesantren Km 2 Cibabat Cimahi Utara, Cimahi 40513 Jawa Barat, Indonesia, 2025)
The purpose of this study is to implementation of Activity Based Management (ABM) in improving production cost efficiency. The data used were primary data and secondary data obtained from UMKM Bengkel Las Karya Indah 2, consisting of sales data, production data, raw material costs, direct labor costs, and factory overhead costs in 2024. The data collection techniques in this study were interviews and documentation. This research uses a quantitative descriptive method. The results showed that the implementation of ABM through the identification of value-added activities and non-value-added activities by reducing and sharing showed an increase in cost efficiency of 1.30% or Rp 1,454,403. This research expects that company management could apply the calculation of the cost of goods produced with the Activity Based Management (ABM) calculation system in increasing production cost efficiency.